1986
DOI: 10.1128/mcb.6.5.1847
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester induces c-sis gene transcription in stem cell line K-562.

Abstract: The phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA) induced megakaryoblastic differentiation and c-sis expression in the human hematopoietic stem cell line K-562. This induction occurred at the transcriptional level, as determined by a nuclear runoff transcriptional assay, and was not a generalized effect of TPA, since the treatment of other hematopoietic cell lines and normal peripheral blood lymphocytes with TPA did not result in the appearance of c-sis mRNA.The study of cellular oncogenes (c-onc) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 27 publications
(24 reference statements)
5
51
0
Order By: Relevance
“…11,[17][18][19] We detected PMA-induced expression of Pyk2 kinase, a protein expressed in megakaryocytes, 45 that was not dependent on the activity of the MEK/MAPK pathway. Since PMA-stimulated differentiation of K562 cells mimics the pathway of natural megakaryocyte precursors, 6 it remains to be detemined whether Pyk2 expression is regulated in a similar fashion in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,[17][18][19] We detected PMA-induced expression of Pyk2 kinase, a protein expressed in megakaryocytes, 45 that was not dependent on the activity of the MEK/MAPK pathway. Since PMA-stimulated differentiation of K562 cells mimics the pathway of natural megakaryocyte precursors, 6 it remains to be detemined whether Pyk2 expression is regulated in a similar fashion in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…16 PMA treatment also leads to the induction of transcription factors such as jun/fos 17 and egr-1 18 and of protooncogenes such as c-ski 19 and c-sis. 11 Treatment of K562 cells with PMA also leads to the p53-independent expression of the cell cycle inhibitor p21waf1/cip. 20 In addition to the effect on cell growth, the changes associated with the adhesive properties of the K562 cells are also evident upon PMA treatment and are likely due, in part, to changes in the cytoskeleton 14 and in integrin expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] One of the well-known mechanisms of mRNA destruction is via mRNA decay, whereby 3'-untranslated regions (UTR) of mRNA that contain AU-rich elements (ARE) are degraded by exo-and endoribonucleases. Recently, it has been shown that ARE sequences often associate with Alu-repeats.…”
Section: S Proteasome Exhibits Endoribonuclease Activity Controlledmentioning
confidence: 99%
“…Relevant to this hypothesis is the finding that TPA induces transcription of cellular protooncogenes, e.g. c-fos (16,17), c-myc (16,18) and c-sis (19). In an attempt to identify the target of transcription regulation by ras, we examined its effect on the promoter of the Rb gene, in expectation of activation of Rb transcription by ras.…”
Section: Introductionmentioning
confidence: 99%